2021
DOI: 10.1039/d0cp05726f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spin glass frustration on exchange bias in NiMn/CoFeB bilayers

Abstract: Exchange bias in ferromagnetic/antiferromagnetic systems can be explained in terms of various interfacial phenomena. Among these spin glass frustration can affect the magnetic properties in exchange bias systems. Here we...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Recently Nayak et al showed that the NiMn/CoFeB possess spin glass like exotic properties at the interface. 31 In the same sample structure, we do show here that there is finite spin current propagation via spin pumping in the heterostructures. The spin pumping voltage reduces to ∼20% up to the NiMn thickness of 40 nm (S4) in comparison to S1.…”
Section: Resultssupporting
confidence: 62%
“…Recently Nayak et al showed that the NiMn/CoFeB possess spin glass like exotic properties at the interface. 31 In the same sample structure, we do show here that there is finite spin current propagation via spin pumping in the heterostructures. The spin pumping voltage reduces to ∼20% up to the NiMn thickness of 40 nm (S4) in comparison to S1.…”
Section: Resultssupporting
confidence: 62%
“…A similar phenomenological picture has also been put forward for other spin-glass systems, where the spin-glass interface or spin-glass state is dominant in modulating the magnitude and behavior of the EB effect [16,23,28,34,35,36,[42][43][44][45]. Most exchange bias fields are generally on the order of 0.01 to 0.1 T, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Such an exponential thermal decay is considered as a fingerprint of the fact that the origin of the H EB and H C is due to the existence of spin frustration; this was previously reported in other systems, including oxides and metals, such as LSMO/LaNiO 3 bilayers [ 18 ]; LSMO/SMO bilayers [ 1 , 19 ]; LSMO/SrIrO 3 (SIO) bilayers [ 15 ]; LSMO/SMO/LSMO trilayers [ 20 ]; La 1-x Ca x MnO 3 FM (x = 0.33)/AFM (0.67) multilayers [ 21 ]; FM/SG Ni/Ni 76 Mn 24 bilayers [ 22 ]; amorphous/crystalline NiFe 2 O 4 ferrite [ 23 ]; NiMn/CoFeB bilayers [ 24 ]; and Co/CuMn bilayers [ 11 ], where the interfacial spin-glass state plays an important role in the EB effect. Thus, the temperature dependence of H EB and H C can be fitted using the phenomenological formulas and , where and are the extrapolation of H EB and H C at zero temperature; T 1 and T 2 are constants.…”
Section: Resultsmentioning
confidence: 99%